Smoothness of generalized solutions of boundary problems of electrodynamics with general material equations - Kurbanov , I. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
The questions of solubility and smoothness of generalized solutions of an electrodynamic boundary problem with general physical equations are studied. An existence and uniqueness theorem is proven and the smoothness of general solutions of the problem is investigated. New a priori estimates are established with the aid of a generalized Gronwall-Bellmann inequality.